2016
DOI: 10.1037/adb0000140
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related visual cues impede the ability to process auditory information: Seeing but not hearing.

Abstract: Studies of visual attention find that drinkers spend more time attending to images of alcohol-related stimuli compared to neutral images. It is believed that this attentional bias contributes to the maintenance of alcohol use. However, no research has examined the possibility that this bias of visual attention might actually impede the functioning of other modalities, such as the processing of accompanying auditory stimuli. This study aimed to determine if alcohol-related images engender greater sensory domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…In order to ensure sufficient statistical power, this recommended sample size was doubled and25 participants were recruited. This sample size and gender ratio is consistent with that reported in previous research (Monem & Fillmore, 2016, n = 25, n = 13 females; Leiva et al, 2015, n = 20, n = 15 females; Vorstius, Radach, Lang, & Riccardi, 2008; n = 24, n = 12 females). Participants were required to be over the legal age of drinking to take part (18 years old in the U.K.) and reported no visual acuity or auditory deficits.…”
Section: Participantssupporting
confidence: 92%
See 2 more Smart Citations
“…In order to ensure sufficient statistical power, this recommended sample size was doubled and25 participants were recruited. This sample size and gender ratio is consistent with that reported in previous research (Monem & Fillmore, 2016, n = 25, n = 13 females; Leiva et al, 2015, n = 20, n = 15 females; Vorstius, Radach, Lang, & Riccardi, 2008; n = 24, n = 12 females). Participants were required to be over the legal age of drinking to take part (18 years old in the U.K.) and reported no visual acuity or auditory deficits.…”
Section: Participantssupporting
confidence: 92%
“…Indeed, previous studies have provided plentiful evidence for the impact of visual alcohol-related stimuli on inhibitory control mechanisms (e.g., Kreusch et al, 2013;Weafer & Fillmore, 2012), yet relatively less research has examined the impact of alcohol-related auditory stimuli on these processes. As an exception, one study has shown that alcohol-related visual cues impede processing of simultaneously presented auditory signals on a multisensory perception task (Monem & Fillmore, 2016). Other research beyond the focus of substance misuse asserts that the impact of auditory cues on visual attention may be contingent upon their relevance to the task at hand (Leiva, Parmentier, Elchlepp, & Verbruggen, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, estudios anteriores han aportado gran cantidad de evidencia para el impacto de los estímulos visuales relacionados con el alcohol sobre los mecanismos de control inhibitorio (e.g., Kreusch et al, 2013;Weafer y Fillmore, 2012), pero relativamente menos estudios han examinado el impacto de los estímulos auditivos relacionados con el alcohol sobre estos procesos. Como excepción, un estudio encontró que los estímulos visuales relacionados con el al-cohol obstaculizan el procesamiento de señales auditivos presentados simultáneamente en una tarea de percepción multisensorial (Monem y Fillmore, 2016). Otros estudios fuera del campo de abuso de sustancias afirman que el impacto de los estímulos auditivos sobre la atención visual podrá estar supeditado a su relevancia para la tarea ejecutada en ese momento (Leiva, Parmentier, Elchlepp, y Verbruggen, 2015).…”
unclassified
“…Es más, se esperaba que los participantes tendrían mayor precisión y rapidez en sus respuestas a estímulos visuales relacionados con el alcohol en ensayos pro-sacádicos cuando estaban expuestos a estímulos auditivos cortos relacionados con el bar (según Leiva et al, 2015). No obstante, durante las tareas anti-sacádicas, esperábamos que los estímulos relacionados con el alcohol interferirían con el rendimiento fijado en un objetivo y disminuirían el control inhibitorio hacia los estímulos visuales relacionados con el alcohol (c.f., Monem y Fillmore, 2016). Esto fue respaldado por el razonamiento que escuchar un sonido relacionado con el alcohol (i.e., audio de un ambiente de bar) debería hacer más significativos para el participante los estímulos relacionados con el alcohol, captando su atención.…”
unclassified